Biomechanical properties and microstructure of neonatal porcine ventricles. (December 2018) - Ahmad, Faizan; Prabhu, Ra﻿j.; Liao, Jun; Soe, Shwe; Jones, Michael D.; Miller, Jonathan; Berthelson, Parker; Enge, Daniel; Copeland, Katherine M.; Shaabeth, Samar; Johnston, Richard; Maconochie, Ian; et al.
Abstract: Neonatal heart disorders represent a major clinical challenge, with congenital heart disease alone affecting 36, 000 new-borns annually within the European Union. Surgical intervention to restore normal function includes the implantation of synthetic and biological materials; however, a lack of experimental data describing the mechanical behaviour of neonatal cardiac tissue is likely to contribute to the relatively poor short- and long-term outcome of these implants. This study focused on characterising the mechanical behaviour of neonatal cardiac tissue using a porcine model, to enhance the understanding of how this differs to the equivalent mature tissue. The biomechanical properties of neonatal porcine cardiac tissue were characterised by uniaxial tensile, biaxial tensile, and simple shear loading modes, using samples collected from the anterior and posterior walls of the right and left ventricles. Histological images were prepared using Masson's trichrome staining, to enable assessment of the microstructure and correlation with tissue behaviour. The mechanical tests demonstrated that the neonatal cardiac tissue is non–linear, anisotropic, viscoelastic and heterogeneous. Our data provide a baseline describing the biomechanical behaviour of immature porcine cardiac tissue. Comparison with published data also indicated that the neonatal porcine cardiac tissue exhibits one-half the stiffness of mature porcine tissue in uniaxial extension testing, one-third in biaxial extension testing, and one-fourth stiffness in simple shear testing; hence, it provides an indication as to the relative change in characteristics associated with tissue maturation. These data may prove valuable to researchers investigating neonatal cardiac mechanics. Graphical abstract: Highlights: Maturation appears to increase uniaxial, biaxial and simple shear stiffness Neonatal tissue exhibits non-linear, anisotropic, and heterogeneous behaviour. The anterior walls are stiffer than the posterior walls, in both ventricles.